Performance Evaluation of Modelling and Simulation of Lead Acid Batteries for Photovoltaic Applications - A. Selmani; A. Ed-Dahhak; M. Outanoute; A. Lachhab; M. Guerbaoui; B. Bouchikhi (Institute of Advanced Engineering and Science, 2016)
Lead-acid batteries have been the most widely used energy storage units in stand-alone photovoltaic (PV) applications. To make a full use of those batteries and to improve their lifecycle, high performance charger is often required. The implementation of an advanced charger needs accurate information on the batteries internal parameters. In this work, we selected CIEMAT model because of its good performance to deal with the widest range of lead acid batteries. The performance evaluation of this model is based on the co-simulation LabVIEW/Multisim. With the intention of determining the impact of the charging process on batteries, the behaviour of different internal parameters of the batteries was simulated. During the charging mode, the value of the current must decrease when the batteries’ state of charge is close to be fully charged.